From Depression to Happiness : a Positive Psychiatry Prescription for Life after Depression. - Messias, Erick (Cambridge Scholars Publisher, 2019)
Psychiatry has developed a number of tools to help manage symptoms of mental disorders, broadly categorized as psychotherapy, or ""talk therapy"", and psychopharmacology, or ""medications"". One question left open in this regard, though, is what to do after those symptoms are controlled? How can those with depression be helped to build a better life after the remission of symptoms? Weaving together Positive Psychology and Aristotelian philosophy, this book details an approach to creating a path towards a flourishing life. Building on the two translations of the Greek term ""Arete"", virtue and.